Human Modeling and Passivity Analysis for Semi-Autonomous Multi-Robot Navigation in Three Dimensions - Takeshi Hatanaka; Takahiro Mochizuki; Takumi Sumino; Jose M. Maestre; Nikhil Chopra (IEEE Open Journal of Control Systems)
In this article, we study a one-human-multiple-robot interaction for human-enabled multi-robot navigation in three dimensions. We employ two fully distributed control architectures designed based on human passivity and human passivity shortage. The first half of this article focuses on human modeling and analysis for the passivity-based control architecture through human operation data on a 3-D human-in-the-loop simulator. Specifically, we compare virtual reality (VR) interfaces with a traditional interface, and examine the impacts that VR technology has on human properties in terms of model accuracy, performance, passivity and workload, demonstrating that VR interfaces have a positive effect on all aspects. In contrast to 1-D operation, we confirm that operators hardly attain passivity regardless of the network structure, even with the VR interfaces. We thus take the passivity-shortage-based control architecture and analyze the degree of passivity shortage. We then observe through user studies that operators tend to meet the degree of shortage needed to prove closed-loop stability.